Farmer boy - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York : HarperTrophy, 1971)
The life of Almanzo Wilder in New York State in the 1860's, before he went west with his family to homestead land and to meet his future wife, Laura Ingalls Wilder.
Horn Book.
Library Journal.
5.0
3-6
Keywords: Wilder, Almanzo -- Fiction; Wilder, Almanzo -- Juvenile fiction; Wilder, Almanzo -- Fiction; Farm life -- Juvenile fiction; Farm life -- Fiction; Farm life -- Fiction